Implementasi Sistem Keamanan Data untuk Proyek Konstruksi Menggunakan Metode Algoritma Rivest Cipher 4 (RC4) Berbasis Android - Kennedy, Calvin Mulia; Rahmad Doni (Universitas Methodist Indonesia, 2025)
Data security is a crucial aspect in managing construction projects, especially for large-scale companies such as PT. Swakarya Perfect. Unprotected data exchange may lead to risks of information leakage, which could impact confidentiality, integrity, and project sustainability. This study aims to implement a data security system using the Rivest Cipher 4 (RC4) algorithm on Android devices, enabling efficient encryption and decryption of construction project data. The research method involves system requirements analysis, application design, RC4 algorithm implementation, and testing of both security strength and application performance. The implementation results show that the developed system can effectively secure construction project data, as the encrypted information cannot be accessed without the proper key. Furthermore, the application demonstrates relatively fast execution time during encryption and decryption processes, making it feasible for mobile use. Therefore, this system contributes to enhancing data security in construction projects at PT. Swakarya Perfect through the application of modern cryptographic technology on Android.